Evaluation of Polyphenol Content and Antioxidant Activities of Some Selected Organic and Aqueous Extracts of Cornsilk (Zea mays Hairs). - Nurhanan, A.R.; Wan Rosli, W. I. (JOMB.org, 2013)
These In this study, the polyphenol content and antioxidant activities of some organic and aqueous extracts of cornsilk were evaluated. Cornsilk powder was extracted with methanol, ethanol, water and ethyl acetate solvent by using soxhlet extraction method. The antioxidant activities of all cornsilk extracts were determined via β-carotene bleaching method, 2,2-diphenyl-2-picrylhydrazyl (DPPH.) radical scavenging, superoxide anion (O2-) radical scavenging and ferric reducing power activity (FRAP). The highest polyphenol content was exhibited by the methanol extract (101.99 mg GAE/g) compared to that of ethanol (93.43 mg GAE/g), water (35.34 mg GAE/g) and ethyl acetate extract (6.70 mg GAE/g). The flavanoid content of cornsilk extracts was in the range of 0.66 to 9.26 mg catechin equivalent/g extract showing the highest content found in the methanol extract. In the antioxidant assays, the methanol extract exhibited the strongest free radical scavenging and reducing activity as compared to the other extracts. In the β-carotene assay, the methanol (66.05%) extract, showed highest bleaching activity compared to the ethanol (52.92%), water (38.65%) and ethyl acetate (26.33%) extract. The IC50 values of methanol, ethanol, water and ethylacetate extract were 140.89 μg/ml, 143.55 μg/ml, 195.21 μg/ml and 411.69 μg/ml respectively. The lowest IC50 in the superoxide scavenging activity was exhibited by the methanol extract (261.41 μg/ml). However, the IC50 value of ethyl acetate extract (412.16 μg/ml) was found lower than that of ethanol (620.91 μg/m) and water extract (1174.54 μg/m). In FRAP assay, the ferric reducing activity of methanol extract reached 56.41% at 1600 μg/ml while ethanol (51.16%), water (35.01%) and ethyl acetate extract (27.21%) exhibited lower reducing activity. These results indicate that cornsilk extracts have shown strong antioxidant activities. With the highest yield of polyphenols and the strongest antioxidant capacity, the methanol extract is highly recommended to be implemented in the pharmaceutical and health related industries to treat oxidative stress related disease.